An equilibrium model of managerial compensation - Michael Magill; Martine Quinzii (University of California, Department of Economics, 2005)
This paper studies a general equilibrium model with two groups of agents, investors (shareholders) and managers of firms, in which managerial effort is not observable and influences the probabilities of firms' outcomes. Shareholders of each firm offer the manager an incentive contract which maximizes the firm's market value, under the assumption that the financial markets are complete relative to the possible outcomes of the firms. The paper studies two sources of inefficiency of equilibrium. First, when investors are risk averse and effort influences probability, market-value maximization differs from maximization of expected utility. Second, because the optimal contract exploits all sources of information for inferring managerial effort, when firms' outputs are correlated the contract of a manager depends on the outcomes of other firms. This leads to an external effect of the effort of one manager on the compensation of other managers, which market-value maximization ignores. We show that under typical conditions these two effects lead to an under-provision of effort in equilibrium. These inefficiencies disappear however if each firm is replicated, and in the limit there is a continuum of firms of each type.
Keywords: 330